Designing an Integrated BSC and IPMS Model Performance Optimization - Nida An Khofiyah; Hasyrani Windyatri (Universitas Islam Raden Rahmat, Malang, 2025)
This study aims to design a performance measurement model by integrating two performance measurement methods, namely the Balanced Scorecard (BSC) and Integrated Performance Measurement Systems (IPMS), to optimize the company's performance. This approach is expected to provide a comprehensive view of the company's performance by combining financial and non-financial indicators and ensuring strategic alignment. The research approach used is descriptive-analytical (literture review), which aims to provide an overview of the performance measurement model design by integrating the Balanced Scorecard (BSC) and Integrated Performance Measurement Systems (IPMS). The study will identify how the integration of these two systems can improve productivity and operational effectiveness. The expected outcome is sustainable performance improvement and productivity enhancement through the implementation of a holistic and integrated performance measurement framework. The novelty of this research lies in the absence of a performance measurement model that combines both methods to measure company performance. The research results in a performance measurement model design that can be implemented to optimize performance in an industry.